Desarrollo de un sistema web de administración y visualización de alertas en tiempo real con notificación vía mensaje de texto y una aplicación móvil con geolocalización de emergencias médicas para la Cruz Roja-Loja. - Carpio Encalada, Johana Marlene, Rosa Virginia Faicán Cango (2016)
This present project to end of career describes in detail the development of a web sistema for admin and displaying medical alerts in real time with notification via text message and a móvil aplication with geolocation for the “Board Loja provincial Red Cross” allowing the institution develop his activities of atention pre-hospitalary of way timely developing an application that offer: send alerts of medical emergencies, panic button, user registration, registre and update of medical history. Searching the fulfillment of the objetives raised have been used techniques of recollection to information as direct observation and interview with the coordinator to Disaster Risk Management for the analysis and interpretation of information were used,bibliographical method, scientific, inductive and deductive . This present project consist two parts a web part for displaying medical alerts, user admin, blacklist, and statistics developed under the same programming language php , using as tools Codeigniter, Ajax and Javascript tolos, the móvil part developed under the Java programming language using tools like Eclipse, Google APIs, SDK, Netbeans, Glassfish for the implementation of Web services. The use of MySQL for the database and phpMyAdmin for the respective tests. It has made use Iconix methodology for the development of this present project, because it makes use of diagrams and documentation allowing to have an overview of the functioning of both the Web system as the Android application, simplifying thereby processes